Integrated Design Analysis of Building Service Systems for Energy-Efficient Retrofitting: A Case Study of the Department of Architecture and Built Environment’s E. ON House in the UK. - Yang, Ziyi (International Journal of Electric Power and Energy Studies, 2025)
This comprehensive report systematically addresses the fundamental building service design requirements for the E. ON House, a flagship sustainable architecture project at the University of Nottingham’s Department of Architecture and Built Environment. Through quantitative analysis of winter design heat losses (both fabric and ventilation) across all thermal zones, we establish the baseline parameters for developing a gas-fired low-temperature hot water (LTHW) central heating system incorporating condensing boiler technology with integrated thermal storage capacity. The design methodology extends to indirect domestic water supply systems with hydraulic decoupling, dual drainage networks compliant with BS EN 12056 standards, and illuminance-optimized LED lighting schemes achieving CIBSE LG7 compliance. A centralized building management system with zoned climate control completes the integrated solution. This multidisciplinary approach demonstrates 23-28% energy efficiency improvements over conventional systems through heat recovery mechanisms, adaptive lighting controls, and optimized hydraulic balancing, positioning the project as a replicable model for low-carbon institutional buildings.